2000
DOI: 10.1103/physrevlett.84.5892
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from Glassy to Inhomogeneous-Ferroelectric Nonlinear Dielectric Response in Relaxor Ferroelectrics

Abstract: The temperature dependence of the dielectric nonlinearities in a PMN single crystal and in 9/65/35 PLZT ceramics has been determined by measuring the first and third harmonic response as well as the dielectric behavior as a function of the dc electric field. In zero field a paraelectric-to-glass, and, in a high enough dc field, a glass-to-ferroelectriclike crossover in the temperature dependence of the nonlinear response have been observed. Both crossovers agree with the predictions of the spherical random-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
76
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 21 publications
13
76
1
Order By: Relevance
“…Thus, it can be observed experimentally an anomalous behavior of ⌬ dc on the high-temperature side of the peak, where the frequency dispersion is weak. This has, indeed, been found in PMN single crystal and PLZT ceramics, 29 supporting the assumption that these systems can be described as a special kind of dipolar glass, namely, the spherical glass. Namely, the scaling theory of the second order phase transition predicts that ⌬ dc should vanish at the ferroelectric transition and diverges at the freezing transition in dipolar glasses, as indeed observed in the experimental results.…”
Section: B DC Nonlinear Dielectric Responsesupporting
confidence: 64%
“…Thus, it can be observed experimentally an anomalous behavior of ⌬ dc on the high-temperature side of the peak, where the frequency dispersion is weak. This has, indeed, been found in PMN single crystal and PLZT ceramics, 29 supporting the assumption that these systems can be described as a special kind of dipolar glass, namely, the spherical glass. Namely, the scaling theory of the second order phase transition predicts that ⌬ dc should vanish at the ferroelectric transition and diverges at the freezing transition in dipolar glasses, as indeed observed in the experimental results.…”
Section: B DC Nonlinear Dielectric Responsesupporting
confidence: 64%
“…It was also found that with zero electric field cooling, PMN undergoes a transition into a random-bond-driven glassy state instead of a ferroelectric state. 21 This system has been intensively investigated in recent years, 22,23 and a more detailed description on this compound can be found in the review article by Ye. 20 Until recently the accepted picture was that PMN remains cubic through its apparent T C of 220 K. The recent neutron scattering paper by Wakimoto et al 24 changed the picture.…”
Section: Discussionmentioning
confidence: 99%
“…Neglecting harmonics higher than the order of a considered susceptibility may lead to artificial effects. The next important point is the simultaneous measurement of all displacement current components, which considerably improves the accuracy of the measured susceptibilities (Bobnar et al, 2000). In case that the phase shifts of the displacement current harmonics are known it is possible to calculate the real, χ i ′, and imaginary, χ i ″, parts of all susceptibilities.…”
Section: Methods Of Measurement Of Nonlinear Dielectric Responsementioning
confidence: 99%